Điều kiện hình thành (P/T) của các thành tạo Magma Granitoid phức hệ Điện Biên và Sông Mã - Anh, Trần Tuấn; Hòa, Trần Trọng; Ý, Nguyễn Viết (Vietnam Journal of Earth Sciences, 2005)
Geobarometric calculation of amphiboles from Dien Bien and Song Ma granitoids by different methods gives lithospheric pressures : 2.9÷3.72 ±0.7 kbar, and 1.36÷1.82 ±0.3 kbar for Dien Bien and Song Ma, respectively. Amphibole-plagioclase geothermometry gives a range of 682 - 781 oc to Dien Bien granitoid and 752 oc to Song Ma. The calculated pressures of Dien Bien’s rocks reflect the initial crystallization of magma chamber, whilst Song Ma’s rock represented latter crystallization period. The magma chambers are situated nearsolidus of typical granite, in the field of mantle wedge of a subduction zone. The average uplift rates are 0.004 - 0.006 cm/year for Dien Bien complex, and 0.002 - 0.0025 em/year for Song Ma’s rocks, which imply that they were located at different position on the subduction zone.